Natural weathering mechanism of isotatic polypropylene under different outdoor climates in China. (December 2017) - Xiong, Jian; Liao, Xia; Zhu, Jingjun; An, Zhu; Yang, Qi; Huang, Yajiang; Li, Guangxian
Abstract: In order to explore the natural weathering mechanism of isotatic polypropylene (iPP) served in different outdoor climates, iPP samples were exposed to four typical climate conditions of China for four years. The microstructural changes of iPP were investigated by positron annihilation lifetime spectroscopy (PALS), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimeter (DSC) and wide-angle X-ray diffraction (WAXD). As the degradation processed, the molecular defects such as carbonyl and hydroxyl groups increased. Because of the formation of the new imperfect crystal caused by chemi-crystallization, the crystallinity increased initially and then reached a plateau. Due to the increase of crystallinity, the amounts of defects in crystalline-amorphous interfacial phase increased and the concentration of free volume holes decreased with exposure time. In addition, the interaction between functional groups constrained the mobility of molecular segments, which persistently decreased the size of free volume holes. The results showed that the freed molecule segments released by chain scission formed new crystals in the amorphous region during the degradation process. In addition, the similar microstructural changes of iPP weathered in different stations showed the similar degradation mechanism. Furthermore, the influence of the temperature on the degradation rate of iPP was more significant than other environmental factors. Highlights: Isotatic polypropylene is investigated by exposing to different outdoor climates for four years. PALS is used to investigate the mechanism of chemi-crystallization and free volume change. The interaction between functional groups decreases the size of free volume holes.